Crimes of passion since Shakespeare: red mist rage unmasked - Howe, Adrian (Routledge, 2023)
Explores 'crimes of passion' through Shakespeare texts.Interdisciplinary approach.Will appeal to feminist and socio-legal scholars, criminologists and those working in the fields of law and literature, legal theory and Shakespeare studies